Critical State of Energy Metabolism in Brain Slices: The Principal Role of Oxygen Delivery and Energy Substrates in Shaping Neuronal Activity - Ivanov, Anton; Zilberter, Yuri (Frontiers in Neuroenergetics, 2011)
The interactive vasculo-neuro-glial system controlling energy supply in the brain is absent in vitro where energy provision is determined by experimental conditions. Despite the fact that neuronal activity is extremely energy demanding, little has been reported on the state of energy metabolism in submerged brain slices. Without this information, the arbitrarily chosen oxygenation and metabolic provisions make questionable the efficient oxidative metabolism in slices. We show that in mouse hippocampal slices (postnatal day 19–44), evoked neuronal discharges, spontaneous network activity (initiated by 4-aminopyridine), and synaptic stimulation-induced NAD(P)H autofluorescence depend strongly on the oxygen availability. Only the rate of perfusion as high as 15 ml/min (95% O2) provided appropriate oxygenation of a slice. Lower oxygenation resulted in the decrease of both local field potentials and spontaneous network activity as well as in significant modulation of short-term synaptic plasticity. The reduced oxygen supply considerably inhibited the oxidation phase of NAD(P)H signaling indicating that the changes in neuronal activity were paralleled by the decrease in aerobic energy metabolism. Interestingly, the dependence of neuronal activity on oxygen tension was clearly shifted toward considerably larger pO2 values in slices when compared to in vivo conditions. With sufficient pO2 provided by a high perfusion rate, partial substitution of glucose in ACSF for β-hydroxybutyrate, pyruvate, or lactate enhanced both oxidative metabolism and synaptic function. This suggests that the high pO2 in brain slices is compulsory for maintaining oxidative metabolism, and glucose alone is not sufficient in fulfilling energy requirements during neuronal activity. Altogether, our results demonstrate that energy metabolism determines the functional state of neuronal network, highlighting the need for the adequate metabolic support to be insured in the in vitro experiments.